Energy-Level Interpretation of Carbazole Derivatives in Self-Assembling Monolayer - Grzibovskis, Raitis; Aizstrauts, Arturs; Pidluzhna, Anna; Marcinskas, Mantas; Magomedov, Artiom; Karazhanov, Smagul; Malinauskas, Tadas; Getautis, Vytautas; Vembris, Aivars (MDPI, 2024)
Energy-level alignment is a crucial factor in the performance of thin-film devices, such as organic light-emitting diodes and photovoltaics. One way to adjust these energy levels is through chemical modification of the molecules involved. However, this approach may lead to unintended changes in the optical and/or electrical properties of the compound. An alternative method for energy-level adjustment at the interface is the use of self-assembling monolayers (SAMs). Initially, SAMs with passive spacers were employed, creating a surface dipole moment that altered the work function (WF) of the electrode. However, recent advancements have led to the synthesis of SAM molecules with active spacers. This development necessitates considering not only the modification of the electrode's WF but also the ionization energy (IE) of the molecule itself. To measure both the IE of SAM molecules and their impact on the electrode's WF, a relatively simple method is photo-electric emission spectroscopy. Solar cell performance parameters have a higher correlation coefficient with the ionization energy of SAM molecules with carbazole derivatives as spacers (up to 0.97) than the work function of the modified electrode (up to 0.88). Consequently, SAMs consisting of molecules with active spacers can be viewed as hole transport layers rather than interface layers. --//-- This is an opne-access article Grzibovskis, R.; Aizstrauts, A.; Pidluzhna, A.; Marcinskas, M.; Magomedov, A.; Karazhanov, S.; Malinauskas, T.; Getautis, V.; Vembris, A. Energy-Level Interpretation of Carbazole Derivatives in Self-Assembling Monolayer. Molecules 2024, 29, 1910. https://doi.org/10.3390/molecules29091910 published under the CC BY 4.0 licence.
The “Development of Semi-Transparent Bifacial Thin Film Solar Cells for Innovative Applications” benefits from a EUR 999372 grant from Iceland, Liechtenstein, and Norway through the EEA Grants. The aim of the project is to develop a new approach based on novel materials, structures, and production technologies, which are the key to further increasing the share and range of application of PV in areas with sub-average sunlight, including Baltic and Nordic countries. Therefore, the development of resource-saving, cost-effective, and efficient PV devices is a primary challenge of this project. The project contract with the Research Council of Lithuania (LMTLT) is S-BMT-21-1(LT08-2-LMT-K-01-003). This work was supported by VIAA project No. 1.1.1.2/VIAA/4/20/592.Institute of Solid-State Physics, University of Latvia, has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART².
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; ionization energy; photoelectron emission spectroscopy; self-assembling monolayer; work function